Did Global Warming and Climate Change Cause the Degradation of Lake Chad, Africa's Most Important 'Ecological Catastrophe'? - Dike, Enwere; Dike, Ngozi (Review of Environment and Earth Sciences, 2018)
This paper explores six hypotheses/theories on Lake Chad’s degradation: i) natural climate variation; ii) anthropogenic climate change compounded the effects of the Sahel drought; iii) unregulated exploitation of Lake Chad’s hydrologic system overdrew the regenerative potential of the lake system; iv) high rates of deforestation in the tropical rain forest belt of West-Central Africa shifted the rain belt Southwards; v) pressure from rapidly expanding human and livestock populations exceeded the carrying potential of the Lake Chad ecosystem; and vi) anthropogenic aerosol emissions in the northern hemisphere shifted the tropical rain-belt southwards. The evidence shows that there is no single-cause explanation for Lake Chad’s degradation; rather the influence of global warming and climate change compounded those from pre-existing drought conditions and non-climate factors e.g unregulated exploitation of Lake Chad’s hydrologic system to degrade the lake.